Design Science: Perspectives from Europe European Design Science Symposium EDSS 2012, Leixlip, Ireland, December 6, 2012Revised Selected Papers - Helfert, Markus; Donnellan, Brian (Communications in Computer and Information Science, 2013)
This book constitutes the refereed proceedings of the European Design Science Symposium, EDSS 2012 held in Leixlip, Ireland, in December 2012 which was held in conjunction with the Intel European Research and Innovation Conference, ERIC 2012. The 14 papers (4 invited papers and 10 full papers) presented were carefully reviewed and selected from various submissions. The papers cover the following topics: software, formal logic, rigorous mathematics, informal natural language descriptions.